Thermodynamic comparison of solar methane reforming via catalytic and redox cycle routes. (February 2021) - Bulfin, B.; Ackermann, S.; Furler, P.; Steinfeld, A.
Highlights: Comparison of methane reforming via catalytic and redox chemical looping routes. Phase equilibrium methodology for solid gas reactions to model a fixed bed. A case study of both solar reforming routes coupled to a methanol synthesis plant. Abstract: Thermochemical methane reforming to syngas is performed on a massive scale in the chemical industry, providing feedstock for many chemical processes such as hydrogen, ammonia and methanol production. The high temperature process heat required for the endothermic reforming reaction could be supplied by conentrated solar energy, in a hybrid solar-fossil process. This can be achieved by re-designing conventional reforming technologies to utilize solar energy as the heat source. Another possible approach is to use a two-step metal oxide redox cycle. Here we compare the two solar thermochemical reforming routes, namely redox reforming and catalytic reforming using thermodynamic analysis and discuss the prospects for both technologies with a focus on methane conversion extents, syngas composition, and energy conversion efficiencies. Further processing of the syngas to liquid fuels is also discussed, in order to highlight how these processes can fit together with gas-to-liquids technologies. The analysis highlights that the redox cycle approach could produce a higher quality syngas, but at the expense of additional thermodynamic constraints, which are sensitive to carbon formation, and also lead to a greater energy demand relative to catalytic reforming.